Kemampuan Komunikasi Anak Autisme setelah Pemberian Mainan Squisy - Astri Widiarti; Angelina Novia Toemon; Dian Mutiasari; Dedy Baboe (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
In general, the social interactions of children with autism are closely related to how the children with the disorder communicate. Failure to developing social interaction makes children with autism unable to make eye contact with their interlocutors, tend to isolate themselves from social interaction, therefore it is very necessary to minimize difficulties, obstacles/weaknesses so that children with autism can carry out social interactions. Squishy is a toy that has pores like a sponge, has a soft texture, dan elastic, it also has the ability to return to its original form. Annaliese Griffin, A New York writer claimed that Squishy could be used as a medium to developing motor skills, and through Squishy’s soft texture, it also could be used to developing children's sense of touch. Children with autism can communicate with themself, creating an imaginary friend, or inviting their parents to participate doing role-playing together, it also could be a place for to children carry out social interaction because they play with their friends. The purpose of The Study is to understand the communication skills of children with autism development after given them Squishy Toys. The research design used in this study is a quasi-experimental study that aims to identify the effect of playing squishy therapy on improving communication development in autistic children with a one-group pre-post test design approach, namely using one group of research subjects with pre-and post-treatment observations. Giving Squishy Toys has a positive impact on the development of communication skills for children with autism. This is because based on the previous study and after being given the Squishy toys treatment, it has a significant relationship.